2018
DOI: 10.1038/s41598-018-32574-0
|View full text |Cite
|
Sign up to set email alerts
|

Molecular diversity and antimicrobial susceptibility of Listeria monocytogenes isolates from invasive infections in Poland (1997–2013)

Abstract: The epidemiology of invasive listeriosis in humans appears to be weakly characterized in Poland, the sixth most populous member state of the European Union. We obtained antimicrobial susceptibility data, PCR-serogroups and genotypic profiles for 344 invasive isolates of Listeria monocytogenes, collected between 1997 and 2013 in Poland. All isolates were susceptible to the 10 tested antimicrobials, except one that was resistant to tetracycline and minocycline and harbored the tet(M), tet(A) and tet(C) genes. Ov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
25
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(37 citation statements)
references
References 49 publications
8
25
0
4
Order By: Relevance
“…This confirms the previous findings that meat products may be a potential source of L. monocytogenes associated with human infections (Buchanan et al, 2017). Furthermore, the present analysis also showed that isolates belonging to five cgMLST types found in food (LI-SL1-ST1-CT1385, LI-SL1-ST1-CT322, LI-SL2-ST2-CT4382, LI-SL6-ST6-CT461, LI-SL6-ST6-CT443) were previously identified among human listeriosis isolates in Poland (Kuch et al, 2018) and other European countries (Denmark and France) (Moura et al, 2016(Moura et al, , 2017. The close genetic distance between isolates within each cgMLST suggests a possible epidemiological link.…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…This confirms the previous findings that meat products may be a potential source of L. monocytogenes associated with human infections (Buchanan et al, 2017). Furthermore, the present analysis also showed that isolates belonging to five cgMLST types found in food (LI-SL1-ST1-CT1385, LI-SL1-ST1-CT322, LI-SL2-ST2-CT4382, LI-SL6-ST6-CT461, LI-SL6-ST6-CT443) were previously identified among human listeriosis isolates in Poland (Kuch et al, 2018) and other European countries (Denmark and France) (Moura et al, 2016(Moura et al, , 2017. The close genetic distance between isolates within each cgMLST suggests a possible epidemiological link.…”
Section: Discussionsupporting
confidence: 83%
“…cgMLST profiles were grouped into cgMLST types (CTs) and sublineages (SLs), using the cut-offs of 7 and 150 allelic mismatches, respectively, as previously described (Moura et al, 2016). The cgMLST profiles obtained in this study were also compared with those from 55 PCR-serogroup IVb and 8 PCR-serogroup IIb publicly available genome sequences of L. monocytogenes isolated from patients in Poland (Kuch et al, 2018). All calculations were made with the method described above.…”
Section: Mlst and Cgmlst Characterizationmentioning
confidence: 99%
See 1 more Smart Citation
“…Listeria monocytogenes faecal shedding in cattle was not confirmed, but this might be a result of the limited number of faecal samples collected on a single date. Although CC11 is not one of the most prevalent CCs in human (Maury et al ; Kuch et al ) and animal (Dreyer et al ; Steckler et al ) clinical isolates, it has been associated with ruminant neurolisteriosis cases (Dreyer et al ).…”
Section: Discussionmentioning
confidence: 99%
“…As previously reported, resistance to the clinically used antibiotics is rare in clinical isolates of L. monocytogenes [21][22][23], however, recent studies report increasing numbers of antibiotic-resistant environmental isolates, including isolates from animals, food and food-processing plants [24][25][26]. This observation is alarming since there is evidence that the increase of minimal inhibitory concentrations (MIC) observed in environmental strains also manifested in clinical strains later on [27].…”
Section: Introductionmentioning
confidence: 97%